Heidi West erlund, Sidsel Karls en, Heidi Partt i (Eds.) Visions for Intercultural Music Teacher Education, Springer, Cham 2020, pp. 224 - Adamczewski, Jakub (Studia Edukacyjne, 2021)
Heidi West erlund, Sidsel Karls en, Heidi Partt i (Eds.) Visions for Intercultural Music Teacher Education, Springer, Cham 2020, pp. 224